Eltrombopag, oral immunosuppressant and androgen combination therapy in twelve patients with refractory severe aplastic anemia. Issue 1 (1st January 2020) - Gao, Qingyan; Zhang, Li; Zhao, Xin; Zhu, Yangmin; Peng, Guangxin; Li, Yang; Li, Yuan; Li, Jianping; Song, Lin; Ye, Lei; Fan, Huihui; Zhou, Kang; et al.
ABSTRACT: Objective : Eltrombopag monotherapy or eltrombopag combined with immunosuppressant has achieved robust hematologic responses in severe aplastic anemia (SAA). In patients with refractory SAA, for whom hematopoietic stem cell transplantation is unavailable, we attempted to combine eltrombopag with oral immunosuppressant and androgen, to further improve hematologic response. Methods : We collected and analyzed data retrospectively from twelve refractory SAA cases who had received combination therapy of eltrombopag, oral immunosuppressant and androgen. All these patients had received intensive immunosuppressive treatment (IST) for more than 6 months and were evaluated as nonresponders. Results : A total of 12 SAA patients were treated with a combination of eltrombopag, an oral immunosuppressant (cyclosporine, N = 9; tacrolimus, N = 3) and androgen. The median maximum dose of eltrombopag was 75 mg/day (range, 75–150). After a median follow-up of 8.5 months (7–23), the overall response rate (ORR) was 42% (5/12, including trilineage, N = 4; hemoglobin + platelet, N = 1). Two of 5 responders reached normal blood counts. Optimal hematological response rates were reached at 6 months. The median increase in neutrophil, hemoglobin and platelet count were 1.64 × 10 9 /L (0.71–2.66), 53 g/L (25–66.5) and 25 × 10 9 /L (14–230), respectively. In general, the combination therapy was well tolerated; however, two patients suffered from non-lethal upper extremity venous thrombosis when they were platelet transfusion-dependent. Conclusion : Eltrombopag, oral immunosuppressant and androgen combination therapy in patients with IST-refractory SAA is feasible and could restore multi-lineage hematopoiesis. Thrombosis risk of eltrombopag still needs to be monitored.